"Vi kan inte göra hipp som happ": Åklagares formuleringar av en objektiv ordning (Sociologisk Forskning, 2006)
The claim that politics, economics, and personal and social values are relevant in judicial decision making is not new. However, a shared view among legal practitioners tends to be that most cases are decided in an objective fashion. Drawing on material from two different studies (one on battered women and one on bribery), this paper investigates how prosecutors rely on and actively uphold an institutional discourse portraying the law and legal practice as impartial and fair. The material consists of interviews with Swedish prosecutors. The analysis demonstrates how prosecutors in talk construct ’the law’as a structure of its own, describing the legal system as independently processing its cases in a rather machine-like fashion regardless of the values, beliefs and thoughts of the individual prosecutor. To maintain this idea prosecutors stress professionalism and objectivity. This may also be achieved in a more subtle way, for example by using a vocabulary with “professional-like” enhancing words (judgment, task, obligation etc.), resisting words with the least connection to subjective opinions.
Keywords: prosecutor; objectivity; discourse